Analysis of Implementation Rice Farming Insurance in Indonesia - Ahmad Nawawi (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2023)
The government provides certainty for farming businesses to remain sustainable if risks occur in agricultural businesses, one of which is through assisting with agricultural insurance premiums. This policy is to support the sustainability of agricultural businesses and support food security. This study aims to analyze agricultural insurance policies and their implementation. This study uses a policy development system engineering through meta-analysis. The research locus was conducted nationally, the research object was the rice farming insurance program, and the research data for 2015-2022. Based on the research results, there are challenges in implementing agricultural insurance, namely the low level of farmer participation, relatively small insurance coverage, long claim payments, and lack of outreach to farmers regarding the importance of agricultural insurance. The recommendations in the short-term, policies that must be implemented include simplifying the participant registration process, simplifying the claims process, increasing education and outreach to farmers, and increasing the role of local governments. Meanwhile, medium-term recommendations include bundling the agricultural insurance program with other government assistance programs, improving premium rates based on actual portfolio risk, adjusting coverage based on the amount of premium performance, increasing the share of insurance premiums for farmers, and improving agricultural insurance management institutions.